2017
DOI: 10.18632/oncotarget.23504
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes in human breast cancer cells induced by 4-hydroxyltamoxifen and elucidation of their pathophysiological relevance and mechanisms

Abstract: While tamoxifen (TAM) is used for treating estrogen receptor (ER)a-positive breast cancer patients, its anti-breast cancer mechanisms are not completely elucidated. This study aimed to examine effects of 4-hydroxyltamoxifen (4-OH-TAM) on ER-positive (ER+) breast cancer MCF-7 cell growth and gene expression profiles. MCF-7 cell growth was inhibited by 4-OH-TAM dose-dependently with IC50 of 29 μM. 332 genes were up-regulated while 320 genes were down-regulated. The mRNA levels of up-regulated genes including STA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 86 publications
1
20
0
Order By: Relevance
“…It has been reported that an increase of TG2 expression confers a growth advantage to cancer cells, enabling them to survive in hypoxic conditions. TG2 overexpression seems to be associated with the proliferation and metastasis of various tumours, such as breast cancer, ovarian cancer, lung cancer and colorectal carcinoma [32][33][34][35][36]. Several reports proposed TG2 inhibition as a useful tool for therapeutic approaches.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that an increase of TG2 expression confers a growth advantage to cancer cells, enabling them to survive in hypoxic conditions. TG2 overexpression seems to be associated with the proliferation and metastasis of various tumours, such as breast cancer, ovarian cancer, lung cancer and colorectal carcinoma [32][33][34][35][36]. Several reports proposed TG2 inhibition as a useful tool for therapeutic approaches.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the signi cance in cluster E is rather di cult to interpret. Some groups have previously reported that interferon regulatory factor-1 (IRF1) is critical for TAM-mediated apoptosis, and its related pathway is also up-regulated in TAM-treated cells 28 . IRF1 was shown to induce apoptosis in breast cancer cells 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that TGM2 expression is closely associated with the proliferation and metastasis of various malignant tumor cells (4043). TGM2 expression is increased in breast cancer, ovarian cancer, lung cancer and CRC (4447). Similar to previous findings (45), the present data also demonstrated that TGM2 expression was increased in CRC tissues.…”
Section: Discussionmentioning
confidence: 99%